Responsive self-assembly of tectoRNAs with loop–receptor interactions from the tetrahydrofolate (THF) riboswitch - Mitchell, Charles (Nucleic Acids Res, 2019)
Naturally occurring RNAs are known to exhibit a high degree of modularity, whereby specific structural modules (or motifs) can be mixed and matched to create new molecular architectures. The modular nature of RNA also affords researchers the ability to characterize individual structural elements in controlled synthetic contexts in order to gain new and critical insights into their particular structural features and overall performance. Here, we characterized the binding affinity of a unique loop–receptor interaction found in the tetrahydrofolate (THF) riboswitch using rationally designed self-assembling tectoRNAs. Our work suggests that the THF loop–receptor interaction has been fine-tuned for its particular role as a riboswitch component. We also demonstrate that the thermodynamic stability of this interaction can be modulated by the presence of folinic acid, which induces a local structural change at the level of the loop–receptor. This corroborates the existence of a THF binding site within this tertiary module and paves the way for its potential use as a THF responsive module for RNA nanotechnology and synthetic biology.